The Effect of Percapita Income, Inflation, and 1-Month Time Deposit Interest Rate on the Number of 1-Month Time Deposit at PT. State Savings Bank (BTN) in Indonesia Year 2001-2022 - Marbun, Anita Ardiana (Politeknik Negeri Bengkalis, 2023)
This study aims to investigate the impact of Per Capita Income, Inflation Rate, and 1-Month Time Deposit Interest Rate on the Number of 1-Month Time Deposit at PT. Bank Tabungan Negara (BTN) in Indonesia during the period 2001-2022. The data used in this study is secondary and obtained from published financial statements, including official sources such as the websites of Bank Indonesia, Bank Tabungan Negara, and the Central Statistics Agency. The data collection time span covers the period from 2001 to 2022. This study requires three independent variables, namely Per Capita Income, Inflation Rate, and 1-Month Time Deposit Interest Rate, and also a dependent variable, namely the Number of 1-Month Time Deposit Deposits. The results showed that together, Per Capita Income, Inflation Rate, and 1-Month Time Deposit Interest Rate have a significant impact on the Number of 1-Month Time Deposit Deposits at PT. Bank Tabungan Negara (BTN) in Indonesia. This can be inferred from a statistical F probability value that is lower than the significance level of Î± (0.05), which is 0.0000000 Î± (0.05). More specifically, individual Per Capita Income has been proven to have a significant influence on the Number of 1-Month Time Deposit Deposits at PT. Bank Tabungan Negara (BTN) in Indonesia. However, individually, the Inflation Rate and 1-Month Time Deposit Interest Rate are not proven to have a significant influence on the Number of 1-Month Time Deposit at PT. Bank Tabungan Negara (BTN) in Indonesia.The ability of the three independent variables to explain the dependent variable is measured by an adjusted R-Square value of 0.878021. This indicates that the contribution of the three independent variables to the dependent variable is about 87.8%, while the remaining 12.2% is influenced by other factors not studied in this study.